Investigation Quality of Self Care in Patients Members of Families Which Have Simplex and Multiplex Hepatitis B - A Mehran; Z Monjamed; S Samiei; Z Taheri (Tehran University of Medical Sciences, 2005)
Background & Aim: Family history of one member suffering from hepatitis B of family is one of the most important ways of illness transmission in Iran. Thus attention to quality of self care of patients of hepatitis B family has vital role in prevention and control in family and society. Methods & Materials: This research is descriptive study. Samples of this research included 250 patients which 160 persons belonged to simplex hepatitis B families and 90 persons belonged to multiplex hepatitis B families. Patients refer to the center of blood transfusion organization from all of area of Gillan province. In this study data has collected by patens' questionnaire include: demographic qualifications that were designed in two parts 1- individual qualifications and illness qualifications and questions were about quality self care of drug regimen meal regimen, addictions, precautions standard, fallow up disease and diagnostic quality self care in these groups has been analyzed in SPSS statistical soft ware by statistical tests such as 2 test and fisher test. (p<0.005). Results: Our results show that (%64) patients of simplex family and (85.6%) patients of family multiplex have not suitable quality self care. In response to hypothesises (there is relationship between quality of self care of patiens members in family and increasing of HBSAg cases) findings show that exists meaningful relation between self care about hepatitis B and increasing cases HBSAg in families (p<0.05). Discussion: Regarding to dimensions of quality selfcare about hepatitis B disease has important role in preventing from increasing cases HBSAg in families. Particularly regarding to results of research which indicate unsuitable quality self care of patients about drug regime "diet or therapy" "addictions" follow up disease. Therefore in order to control the hepatitis B in family according to the results of this study it is suggested further efforts should be down. The results of this study can be used for other patients infectious such as hepatitis c and Aids.